O PRAWIE I SĄDACH W GUBERNIACH BIAŁORUSKICH W ŚWIETLE AKTÓW WŁADZ ROSYJSKICH Z 1772 ROKU - Godek, Sławomir (Zeszyty Prawnicze, 2016)
The Law and Courts in the Belarusian Governorates as they Relate to the Acts of the Russian Authorities of 1772 Summary Long before entering into the convention with Austria and Prussia on the partition of the Commonwealth, Catherine II had decided to take action which would lead to the addition in practice of some of the Polish lands to the Empire. The matter of the range of Russian territorial gains and their future organisation was often the subject of discussion during the proceedings of the Soviet pri Vysochayshem Dvorye. In spring 1772 the annexed Polish lands were already to be divided into two governorates – Mogilev and Pskov – headed by governors in the shape of Generals M.V. Kahovski and M.N. Krechetnikov respectively. The entirety of the annexed lands was placed in the care of Governor-General Z.G. Chernyshev. The nomination proclamations issued for the governors on 28th May 1772 were accompanied by the “Nakaz”. This act was of the form of instructions defining the rules for the temporary administration of the annexed provinces, in which an array of detailed questions were dealt with. The document also made reference, albeit fleeting, to issues of a legal nature in the stricter sense. The act abolished torture and severe punishments. The “Nakaz” also maintained the previous courts and judicial proceedings in their previous form, but only in private cases. It excluded crimes infringing citizens’ safety from the courts’ remit, but did not give precise indications on which institutions would take over jurisdiction in these matters. Furthermore, in accordance with the depositions of this act, appeals to lower courts were to be directed to the appropriate – although it did not indicate which – Russian authorities. The previous judicial system and form of court procedure was also confirmed by the proclamation of August 1772 issued for Chernyshev, and also added the “Plakat” to that act. The “Plakat” recommended that courts issue sentences in the name of the emperor.